Current-mode squaring, square-rooting and vector summation circuits - Petchakit, Wijittra; Lorsawatsiri, Anuree; Kiranon, Wiwat; Wongtaychathum, Chariya; Wardkein, Paramote (My University, 2010)
This paper presents new current-mode squaring, square-rooting and vector summation circuits based on the second generation current controlled conveyor (CCCII). Consisting of only CCCIIs as active elements not requiring any external passive elements, all of the proposed circuits are capable of high frequency operation and well suited for IC fabrication. Moreover, the circuits performances are insensitive to temperature and their gains can be easily adjusted by varying the input bias current of CCCII. Finally, the simulation results of the proposed squaring, square-rooting and a two-input vector summation circuits are depicted to confirm the theoretical analysis. © 2009 Elsevier GmbH. All rights reserved.
Keywords: Current controlled conveyor; Square-rooter; Squarer; Vector summation circuit